2022
DOI: 10.3390/jcm11133636
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound (POCUS) as an Extension of the Physical Examination in Patients with Bacteremia or Candidemia

Abstract: Background: In general, transthoracic echocardiography (TTE) is the first diagnostic test used for patients with bacteremia or candidemia and clinical signs of Infective Endocarditis (IE). Point-of-care ultrasound (POCUS) may be used in addition to physical examination for the detection of structural heart disease and valve abnormalities. Objective: To determine the diagnostic accuracy of POCUS for the detection of signs suggestive of IE, including vegetation, valvular regurgitation, structural heart disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…When used to assess for evidence of endocarditis in a high-risk population, POCTE has reasonable diagnostic test accuracy. In a multi-center, cross-sectional study of 258 adults with bacteremia or candidemia, POCTE performed by internists had 77% sensitivity and 94% specificity to detect valvular vegetations against the reference standard of TEE performed by cardiologists [ 16 ]. However, in this patient, the preceding symptoms of malaise and generalized illness were not fully characterized until admission to the intensive care unit, and endocarditis was not otherwise entertained upon initial presentation to the ED with STEMI and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…When used to assess for evidence of endocarditis in a high-risk population, POCTE has reasonable diagnostic test accuracy. In a multi-center, cross-sectional study of 258 adults with bacteremia or candidemia, POCTE performed by internists had 77% sensitivity and 94% specificity to detect valvular vegetations against the reference standard of TEE performed by cardiologists [ 16 ]. However, in this patient, the preceding symptoms of malaise and generalized illness were not fully characterized until admission to the intensive care unit, and endocarditis was not otherwise entertained upon initial presentation to the ED with STEMI and cardiogenic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the comparable performance of SAM on TTE and POCUS images demonstrated the advantage of leveraging the generalization capabilities of foundation models 21 in building AI solutions for the rapidly growing use of POCUS in cardiac imaging 35 . While evaluation on a larger POCUS is required to better evaluate inter-observer variations, we demonstrated a strategy to fine-tune foundation models using readily available and relatively high-quality TTE results knowing that POCUS images usually come with larger variations in operator skill levels, image quality, and scanning modalities [35][36][37][38] . We observed that fine-tuned SAM, similar to MedSAM 24 , can accurately segment cases with weak or missing boundaries, which is more common in POCUS images.…”
Section: Integrating Sam and Future Foundation Models Into Clinical R...mentioning
confidence: 99%
“…Here POCUS should be viewed as a rule-in rather than a rule-out test, with a specificity of 94% in one study, but notably low sensitivity. 35 The utility of lung ultrasound for the diagnosis of pneumonia has been well established, with excellent sensitivity and specificity. 11 Findings supportive of pneumonia include heavily consolidated ("hepatized") lung, subpleural consolidation, dynamic air bronchograms, and the shred sign 11 (Figures 5 and 6, Videos 5 and 6).…”
Section: Pocus For Assessment Of Sepsismentioning
confidence: 99%
“…Here POCUS should be viewed as a rule-in rather than a rule-out test, with a specificity of 94% in one study, but notably low sensitivity. 35 …”
Section: Pocus For Assessment Of Sepsismentioning
confidence: 99%